ANALISIS KESULITAN GURU MATEMATIKA DALAM PEMBELAJARAN DARING PADA MASA PANDEMI COVID-19 - Heri Kusnanto; Padrul Jana (Universitas Pekalongan, 2022)
Learning activities that should be done face-to-face turn into online learning in line with the spread of COVID-19. The core competencies that must be mastered by students should still be completed even with all the limitations of learning. Certainly, in terms of this different learning will bring up difficulties, especially the mathematics teacher as an educator. Therefore, this study aims to describe the difficulties of mathematics teachers in online learning and the solutions to overcome teacher difficulties. This research method is Mixed Methods with Sequential Explanatory Design. The process of collecting data is with questionnaires and interviews, while the instruments used are questionnaires and interview guidelines. Technical analysis of the data using the triangulation method, namely a combination of the results of open statement questionnaires, interviews and field documentation. The results showed that (1) online learning in the planning aspect was found in the difficult category of 8.82%. Online learning in the implementation aspect obtained a difficult category of 23.53%. Online learning in the evaluation aspect obtained a difficult category of 35.29%. The most difficult aspect of online learning for mathematics teachers is the evaluation aspect. In general, female teachers, teachers with teaching years less than 3 years, teachers with the latest education bachelor degree have more difficulty in online learning. Then the teachers who teach in junior high School have more difficulty even though they are not significantly different. (2) the solution to the teacher's difficulty in the planning aspect is that the teacher can determine the application that every smartphone has, namely Whatsapp. The solution to the teacher's difficulties in the implementation aspect is that the teacher can provide additional material in the form of video links and modules so that students can study independently to deepen the material. Teachers can do learning not too early and not too late. The solution to the evaluation aspect is that the teacher can consider attitudes before being treated to online learning and give assignments in the form of a portfolio.